Semantic of the lexical-semantic group with meaning «woman, wife» in German language (based on materials of old texts) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
In article are explored the words of the lexical-semantic group “woman, wife” in different periods of development of German language and the attempt is made to show the evolution of the meanings of one subject group in the process of the development of language. The study is based on the materials of the dictionaries and the original Old High German and Middle High German texts.
Keywords: lexem; semantic, old texts; meaning; Old High German language; Middle High German language